The role of work ethic, work culture, and work-life balance in employee productivity at Trusmi Group - Nadia Sutiani; Ade Solahudin; Eteh Resa Asyifa (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines the influence of work ethic, work culture, and work-life balance on employee productivity at Trusmi Group. As employee productivity represents a critical determinant of organizational competitiveness, particularly in retail and creative industries characterized by dynamic operational environments, understanding the factors that enhance workforce performance is essential for sustainable business success. Employing a quantitative research approach with a causal research design, data were collected through structured questionnaires using a Likert scale from 109 employees selected through simple random sampling from a population of 150 employees. The data were analyzed using multiple linear regression techniques with IBM SPSS Statistics, supported by validity, reliability, and classical assumption testing. The findings reveal that work ethic, work culture, and work–life balance each exert a positive and significant influence on employee productivity. Employees demonstrating stronger work ethics, operating within a supportive organizational culture, and experiencing a healthier balance between professional and personal responsibilities tend to exhibit higher levels of productivity. Furthermore, the three variables collectively contribute substantially to explaining variations in employee productivity, highlighting their complementary role in enhancing workforce performance. These results underscore the importance of fostering a productive organizational environment through the promotion of strong work values, a positive workplace culture, and policies that support employees’ work–life balance. The study contributes to the human resource management literature by providing empirical evidence on the multidimensional factors that drive employee productivity within the retail and creative industry context. Keywords: Work Ethic; Work Culture; Work-Life Balance; Employee Productivity; Human Resource Management